Digital Competency Development of School Administrators Under Buriram Primary Educational Service Area office 2 - Buasi, Ketsaraporn; Sitthisua , Thanyatep; Yordsala, Suphatanakris (Academic MCU Buriram Journal, 2025)
The purposes of this research were: 1) to examine the current level, desired level, and necessity of digital competency among school administrators in Buriram Primary Educational Service Area Office 2, 2) to explore strategies for developing digital competency among school administrators in Buriram Primary Educational Service Area Office 2, and 3) to evaluate the proposed strategies for digital competency development. The research instruments included: (1) a questionnaire assessing the current and desired levels of digital competency among school administrators, (2) a focus group discussion form, and (3) an evaluation form assessing the appropriateness and feasibility of the proposed development strategies. The sample consisted of 143 schools under the Buriram Primary Educational Service Area Office 2, with data collected from 143 school administrators and 10 qualified experts participating in the focus group discussions. Data analysis utilized percentage, mean ( ), standard deviation (S.D.), and the necessity index. The results findings were as follows: 1. The overall current level of digital competency among school administrators was moderate ( = 3.16, S.D. = 0.79) which each section shown the result was also at a moderate level. The overall desired level of digital competency was high ( = 4.46, S.D. = 0.57), with all sections rated at a high level. 2. The order of the needs for developing digital competence of school administrators under the Buriram Primary Educational Service Area Office 2, ranked from most to least important as follows: 1) Creation of digital innovative media (0.472), 2) Ethics and problem solving with digital tools (0.442), 3) Digital technology safety (0.431), 4) Communication and creation of digital collaboration networks (0.405), 5) Use of digital technology (0.393), and 6) Digital literacy and understanding (0.355), respectively. 3. The focus group discussion identified 12 strategies for enhancing digital competency across 6 key factors: digital literacy and comprehension, digital media innovation creation, digital technology utilization, digital communication and collaboration, digital ethics and problem-solving and technology digital security. The results indicated that the overall applicability of the proposed development strategies was at the highest level ( = 4.86, S.D. = 0.35), and their feasibility was also rated at the highest level ( = 4.62, S.D. = 0.54).